2010
DOI: 10.1111/j.1365-3148.2010.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia pneumoniae in peripheral blood mononuclear cells of healthy blood donors in Tehran Regional Educational Blood Transfusion Centre

Abstract: Chlamydia pneumoniae is a common pathogen in the world often causing upper or lower respiratory tract infection and may also be linked to some chronic inflammatory diseases. Recent studies have shown that a high percentage of healthy blood donors harbour Chlamydia DNA and antigens. The objective of this study was to investigate the presence of this microorganism among blood donors. Blood samples were collected between November 2004 and March 2005 from 196 healthy blood donors. Ten millilitre of blood was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Chronic Cpn infection is a risk factor of chronic obstructive pulmonary disease (COPD) (Zhou et al, 2011). Recent studies have shown that a high percentage of healthy blood donors harbor Chlamydia DNA and antigens (Karimi et al, 2010). Higher Cpn infection rates have been observed in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Cpn infection is a risk factor of chronic obstructive pulmonary disease (COPD) (Zhou et al, 2011). Recent studies have shown that a high percentage of healthy blood donors harbor Chlamydia DNA and antigens (Karimi et al, 2010). Higher Cpn infection rates have been observed in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…These include hepatitis B and C viruses, human immunodeficiency virus, human T‐cell leukemia virus, syphilis, West Nile virus, Chagas disease ( Trypanosoma cruzi ), and on selected units, cytomegalovirus (CMV/human herpesvirus‐5) 1‐3 . Thus, while transmission of these infections via transfusion has become exceedingly rare, the risk of transfusion‐transmitted infections for which testing is not currently performed continues to be a concern 4‐8 . Among these untested infectious agents is Epstein‐Barr virus (EBV, also known as human herpesvirus‐4), which in immunocompromised patients, can induce lymphoproliferative disease, a potentially fatal cancer 9‐12 …”
mentioning
confidence: 99%
“…Most bacterial DNA was detected in the blood buffy coat in healthy individuals [ 27 ]. In a significant percentage of healthy donors, PBMC phylum Chlamydiae species Chlamydophila pneumoniae , a human obligate intracellular parasite bacterium and etiologic agent of an atypical pneumonia form [ 55 ], was detected ( Table 2 ). Chlamydiae are known for their unique biphasic life cycle, during which they alternate between two morphological forms: infectious extracellular elementary bodies (EBs) transform into metabolically active intracellular reticulate bodies (RBs) after entering the host cell [ 12 ].…”
Section: Blood Microbiome Localizationmentioning
confidence: 99%